The Morphological, Physiological and Biochemical Effects of Drought in Different Pepper Genotypes - Şebnem Kuşvuran; Sevinç Uslu Kıran; Özlem Altuntaş (Turkish Journal of Agriculture: Food Science and Technology)
Drought stress is one of the most serious abiotic stresses that cause a reduction in plant growth, development and yield in the world. The aim of this study is to reveal the morphological, physiological and biochemical responses of the Demre pepper variety and nine different pepper genotypes against drought stress. Pepper seeds were planted into trays containing peat: perlite (2: 1) mixture. Then, seedlings having two leaves were transferred to plastic pots containing mixture of peat:perlite (2:1) mixture. Drought stress application was started when the plants have four leaves. The control plants were irrigated with nutrition solution. Genotypes were classified according to the severity of leaf damage symptoms by using 0-5 scale. In addition, shoot fresh and dry weight, plant height, stem diameter, leaf number, leaf area, relative water content (RWC), membrane injury index (MII), potassium (K) and calcium (Ca) concentration of shoot, malondialdehyde content (MDA), total chlorophyll and carotenoid, total flavonoid and phenolic content, anitoxidative enzyme activities (superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), ascorbate peroxidase (APX)) were also determined. As a result of the study, it was determined that drought had negative effect in terms of morphological and physiological parameters, and this effect revealed differences among genotypes. While drought stress increased MDA and antioxidative enzyme activity, BIB-6 and BIB-8 genotypes were found to be the most tolerant genotypes among the genotypes examined.